Investigation of Vibration Machine Interaction With Compacted Concrete Mixture - Nesterenko, Mykola; Maslov, Aleksandr; Salenko, Julia (International Journal of Engineering and Technology, 2018)
Dynamic system calculation scheme "Vibrating machine is compacting medium", where the latter is represented as a system with distributed parameters is compiled. As a result of the wave equation of oscillations solution, the law of compacting medium deformation over the entire thickness of the concrete layer is determined depending on the increasing density of the molded mixture, its physico-mechanical characteristics, the thickness of the concrete layer, the mass of the oscillating part of the vibrating machine, the frequency and amplitude of the disturbing force, elastic suspension stiffness and coefficient inelastic resistance. Changes in the compacting concrete medium resistance forces during the vibration compaction, depending on its consistency are determined.Â Â